2007
DOI: 10.2353/ajpath.2007.060576
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Seeding and Cross-Competition in Mouse Apolipoprotein A-II Amyloid Fibrils and Protein A Amyloid Fibrils

Abstract: Murine senile [apolipoprotein A-II amyloid (AApoAII)] and reactive [protein A amyloid (AA)] amyloidosis are reported to be transmissible diseases via a seeding mechanism similar to that observed in the prion-associated disorders, although de novo amyloidogenesis and the progression of AApoAII or AA amyloidosis remain unclear. We examined the effect of co-injection of AApoAII and AA fibrils and multiple inflammatory stimuli in R1.P1-Apoa2(c) mice with the amyloidogenic Apoa2(c) allele. Both AApoAII and AA amylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…Furthermore, it has been shown that AA can cross-seed and cross-compete with other amyloid fibrils, such as that observed for the AApoAII in an induced amyloidosis mouse model [8].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that AA can cross-seed and cross-compete with other amyloid fibrils, such as that observed for the AApoAII in an induced amyloidosis mouse model [8].…”
Section: Discussionmentioning
confidence: 99%
“…Though amyloid fibril formation may be a generic property of polypeptide chains (Dobson, 1999), in vivo, only 26 different proteins are known to form fibrils naturally (Yan et al, 2007). Since amyloidoses are classified by the amassing protein, 26 different types of amyloidosis have been described.…”
Section: Cross-seedingmentioning
confidence: 99%
“…While the build-up of Islet Amyloid Polypeptide (IAPP) in insulin-secreting cells is a hallmark of a substantial proportion of T2D (Hull et al, 2004), the role amyloid IAPP plays in the disease remains unclear. Some 'consider T2D to be a form of islet Alzheimer disease' (Prentki and Nolan, 2006) and even suggest that one of the reasons diabetics have higher rates of Alzheimer's is that pancreatic amyloid fibrils may be cross-seeding amyloid-in their own brains (Yan et al, 2007), though IAPP fails to seed the formation of A (1-40) fibrils in vitro (O'Nuallain et al, 2004). Amyloid deposits (including A and AA) have also been found in arterial atherosclerotic plaques, but the role they play, if any, is likewise unknown (Howlett and Moore, 2006), hindering efforts to understanding the extent of the potential risk associated with dietary amyloid exposure.…”
Section: Cross-seedingmentioning
confidence: 99%
See 1 more Smart Citation
“…These samples were examined under an electron microscope (1200EX or 1400EX; JEOL) with an acceleration voltage of 80 kV. Immunoelectron microscopy was performed using a modified method in parts described previously (51). The preincubated seeds with biotin-labeled a48/65 (N62K) were resuspended in the reaction solution and recentrifuged.…”
Section: Animals B6spret-apoa2mentioning
confidence: 99%